Obesity and Gestational Diabetes in Pregnant Care and Clinical Practice - Poblete, José Andrés; Olmos, Pablo (Current Vascular Pharmacology, 2021)
Obesity and Gestational Diabetes Mellitus (GDM) are the most frequent pathologies affecting mothers and offspring during pregnancy. Both conditions have shown a sustained increase in their prevalence in recent years, and they worsen the outcome of pregnancy and the long-term health of mothers. Obesity increases the risk of GDM and pre-eclampsia during pregnancy and elevates the risk of developing metabolic syndrome in later life. Offspring of obese mothers have an increased risk of obstetric morbidity and mortality and, consistent with the developmental origins of health and disease, a long term risk of childhood obesity and metabolic dysfunction. On the other hand, GDM also increases the risk of pre-eclampsia, caesarean section, and up to 50% of women will develop type 2 diabetes later in life. From a fetal point of view, it increases the risk of macrosomia, large-for-gestational-age fetuses, shoulder dystocia and birth trauma. The insulin resistance and inflammatory mediators released by a hypoxic trophoblast are mainly responsible for the poor pregnancy outcome in obese or GDM patients. The adequate management of both pathologies includes modifications in the diet and physical activity. Drug therapy should be considered when medical nutrition therapy and moderate physical activity fail to achieve treatment goals. The antenatal prediction of macrosomia is a challenge for physicians. The timing and the route of delivery should consider adequate metabolic control, gestational age, and optimal conditions for a vaginal birth. The best management of these pathologies includes pre-conception planning to reduce the risks during pregnancy and improve the quality of life of these patients.
Keywords: treatment